FRI0496 An Open-Label Study to Evaluate Biomarkers and Safety in Systemic Sclerosis (SSC) Patients Treated with Paquinimod (ABR-215757). (10th June 2014) - Hesselstrand, R.; Distler, J.H.; Riemekasten, G.; Törngren, M.; Nyhlén, H.C.; Stenström, M.; Andersson, F.; Eriksson, H.; Sparre, B.; Tuvesson, H.; Distler, O.
Abstract : Background: Paquinimod (ABR-215757) is an oral small molecule compound that belongs to the quinoline-3-carboxamide derivatives, a class of structurally related compounds with immunomodulatory properties. Paquinimod has shown beneficial effects in several autoimmune/inflammatory disease models, including experimental models of systemic sclerosis (SSc). Paquinimod binds the S100A9 protein and disrupts its binding to the pro-inflammatory receptors RAGE and TLR4 (1). Mechanistic studies have shown that paquinimod interferes with accumulation of myeloid cells during inflammation (2, 3). Previous clinical experience consists of two phase I dose escalation safety studies and one exploratory study in SLE patients (4). Objectives: The aims of the present study in SSc patients were to evaluate safety and changes in disease related biomarkers. Methods: Nine patients with a disease duration of 2.0±2.0 (mean ± SD) years and diffuse SSc were treated with paquinimod at 3.0 mg/day for eight weeks in an international, open label, multi-centre study (ClinicalTrials.gov Identifier: NCT01487551 ). The primary endpoint was changes in disease related biomarkers. Skin biopsies were assessed histologically for α-SMA positive myofibroblast counts. Expression of a panel of extracellular matrix genes and pro-fibrotic genes were analysed by real-time PCR. Secondary end-points included adverse events (AE), extent of skin fibrosis (mRSS) and Quality of Life (QoL) assessments. Results: Paquinimod was well tolerated and all patients completed the eight week treatment period. Except for one SAE (peripheral ischemia, considered severe and unrelated to study medication) only mild or moderate AEs, most commonly arthralgia (n=3) and headache (n=3), were reported. Baseline mRSS was 28±10 (mean ± SD) points and as expected, no change in mRSS and QoL measures were observed in this short-term clinical trial. A small but significant reduction of the number of myofibroblasts in the skin was observed after paquinimod treatment compared to baseline (8%, p=0.023). Down-regulation of a number of pro-fibrotic genes such as CCR2, PAI-1, TIMP3, CAV1, CTGF and FN1 was evident after eight weeks of treatment. While no consistent effects on extracellular matrix genes were observed, the expression of several type I IFN-regulated genes also declined in the majority of the patients. The effects on biomarkers are in line with preclinical data in Tsk-1 mice and support that paquinimod could be effective by targeting the innate immune system in SSc. Conclusions: Paquinimod was well tolerated and effects on biomarkers relevant for SSc were observed during treatment. References: Björk et al., PLoS Biol. 2009;7(4):e97. Deronic et al., International Immunopharmacology 2014; 18:290-297. Helmersson et al., Am J Pathol. 2013;182(5):1671-80. Bengtsson et al., Arthritis Rheum 2012; 64:1579-88. Disclosure of Interest: R. Hesselstrand Consultant for: Active Biotech., J. Distler: None declared, G. Riemekasten: None declared, M. Törngren Shareholder of: Active Biotech., Employee of: Active Biotech., H. Nyhlén Shareholder of: Active Biotech., Employee of: Active Biotech., M. Stenström Shareholder of: Active Biotech., Employee of: Active Biotech., F. Andersson Employee of: Active Biotech., H. Eriksson Shareholder of: Active Biotech., Employee of: Active Biotech., B. Sparre Employee of: Active Biotech., H. Tuvesson Shareholder of: Active Biotech., Employee of: Active Biotech., O. Distler Consultant for: Active Biotech. DOI: 10.1136/annrheumdis-2014-eular.4207